2013
DOI: 10.1016/j.evolhumbehav.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of speech rate in conversation predicts cooperation

Abstract: During conversation, interlocutors coordinate their behavior on many levels. Two distinct forms of behavioral coordination have been empirically linked with affiliation and cooperation during or following face-to-face interaction: behavior matching and interpersonal synchrony. Only the latter form constitutes behavioral entrainment involving a coupling between independent oscillators. We present the first study of the association between spontaneously occurring behavioral coordination and postinteraction econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(105 citation statements)
references
References 58 publications
3
102
0
Order By: Relevance
“…Characterizing clinicians’ speech patterns provides an additional key to understanding how clinicians might enhance the patient experience and communication outcomes [34]. We have demonstrated that connectional silences are empirically identifiable through their paralinguistic features, especially dialog rhythm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterizing clinicians’ speech patterns provides an additional key to understanding how clinicians might enhance the patient experience and communication outcomes [34]. We have demonstrated that connectional silences are empirically identifiable through their paralinguistic features, especially dialog rhythm.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings suggest that among other things, this coordination may be related to cognitive mirroring and entrainment, and may reflect interpersonal engagement and presence. Briefly, these functions refer to our mind’s ability to model another person’s actions with or without actually performing them physically [6,3438]. During a connectional silence, speakers may be entrained physically, and the mirroring of each other’s vocal activity before, during, and after each silence may be an indication of a multi-level synchronization that facilitates this emotional exchange [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The "tone" of a conversation, for instance, is not just carried by particular matches between turns, words, or other speech acts. Tone can be partly expressed as an approximate statistical conver gence in, for instance, pitch, loudness, and pace of speech (Manson, Bryant, Gervais, & Kline, 2013;Neumann & Strack, 2000;Webb, 1969). Similarly, regional accents and dialects can be considered as a kind of convergence (Coupland, 1980) in the temporal dy namics of speech over multiple timescales and partly stem from common allophonic variations that are coordinated among popu lations of speakers over countless conversations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, when people observe an interaction partner smiling, they infer that the situation involves corresponding interests, but when an interaction partner expresses anger, they infer that the situation contains conflict (Pietroni, Van Kleef, De Dreu, & Pagliaro, 2008;Reed, Zeglen, & Schmidt, 2012;Van Doorn, Heerdink, & Van Kleef, 2012). Cues of an interaction partner mimicking one's own nonverbal behavior (i.e., gestures and posture), or showing similar emotional responses to one's own, can indicate that a situation requires coordination (e.g., Lakin, Jefferis, Cheng, & Chartrand, 2003;Manson, Bryant, Gervais, & Kline, 2013). Similarly, estimates of own and others' formidability (i.e., the ability to inflict costs or deny benefits; can reliably indicate that one is in a situation with asymmetric power.…”
Section: Functional Interdependence Theorymentioning
confidence: 99%